Preface as a Paratext in Charles Dickens's David Copperfield: A Pragmatic Study - Iman Ra'ouf Muhammad (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2022)
This study is aimed at identifying the pragmatic functions of the preface as a paratext in Chalres Dickens’s David Copperfield. To fulfill this aim, the study adopts an eclectic model combining Searle’s (1979) speech acts, Aristotle’s (2007) rhetorical theory, Levinson’s (1983) person deixis and Hyland’s (1998) reliability hedges. Through the descriptive qualitative approach, the data analysis shows that Dickens employs only three types of speech acts (representative, commissive and expressive), three modes of persuasion (pathos, logos and ethos), the first and third person deixis, and two reliability hedges. The analysis also brings into light that Dickens employs these linguistic tools to gain readers’ interest, sympathy and trust, and reinforce his credibility as an author, narrator and participant in the world of the novel they are about to enter. The results detect that the preface offers a few glimpses about the work in hand, and functions as a perception shaping device. تهدف الدراسة إلى التعرف على الوظائف التداوليّة للمُقدّمة باعتبارها عتبةً نصيّة في رواية دايڤد کوبرفيلد للکاتب تشارلز ديکينز. ومن أجل تحقيق هذا الهدف، تتبنى الدراسة نموذجًا انتقائيًا يجمع بين الأفعال الکلامية (Searle, 1979) والنظرية البلاغية (ِAristotle, 2007) والإشارات الشخصية (Levinson, 1983) وأساليب التحوّط الجديرة بالثقة (Hyland, 1998). وقد أظهر تحليل البيانات الذي تم إجرائه باتباع المنهج النوعيّ الوصفيّ أنّ ديکينز استخدم ثلاثة أنواعٍ فقط من الأفعال الکلامية (التمثيلية والإلزامية والتعبيرية)، وثلاثة أنماطٍ للإقناع (العاطفة والمنطق والأخلاقيات)، وإشارات شخصية بصيغة المُتکلِّم والغائب، واثنين من عبارات التحوّط الجديرة بالثقة. کما أوضح التحليل أنّ ديکينز قام بتوظيف هذه الأدوات اللُغوية لکسب اهتمام القراء وتعاطفهم وثقتهم، ولتعزيز مصداقيته کمؤلِّف وراوٍ ومُشارِک في عالَم الراوية الذي هم على وشک الولوج إليه. وتُشير النتائج إلى أنّ المُقدّمة تعرض بعض اللمحات عن العمل المُتناوَل، وکذلک تعمل کأداةٍ  لتشکيل التصوّرات.